THE ROLE OF LANGUAGE AND SOCIAL RELATIONS IN INTERCULTURAL COMMUNICATION - Abdukarimova Madina; Nabiyeva Xilola (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This article discusses the science of sociolinguistics, language and social relations, the impact of changes in society on language, the influence of other languages in intercultural communication.